Against the Dark: Antiblackness in Education Policy and Discourse. Issue 1 (2nd January 2016) - Dumas, Michael J.
Abstract : I argue that analyses of racial(ised) discourse and policy processes in education must grapple with cultural disregard for and disgust with blackness. This article explains how a theorization of antiblackness allows one to more precisely identify and respond to racism in education discourse and in the formation and implementation of education policy. I contend that deeply embedded within racialized policy discourses is not merely a concern about disproportionality or inequality, but also a concern with the bodies of Black people, the signification of (their) Blackness, and the threat posed by the Black to the educational well-being of other students. Using school (de)segregation as an example, I demonstrate how policy discourse is informed by antiblackness, and consider what an awareness of antiblackness means for educational policy and practice.